STATE SUPPORT MEASURES OF JOB CREATION IN THE AGROINDUSTRIAL COMPLEX OF UZBEKISTAN - Djumanova Rano Fayzullaevna; Kholmedova Nodirabegim Khurshidovna (Scholar Express Journal, 2024)
The article examines the creation of jobs in the agriculture of Uzbekistan, employment in agriculture, and the impact on poverty reduction, since 80% of the low-income population of Uzbekistan live in rural areas. Measures of state support for creating jobs in the agro-industrial complex of Uzbekistan are being considered
Keywords: agricultural sector; employment; state policy; government spending